Mycroft Holmes. 1 - Abdul-Jabbar, Kareem, 1947-; Obstfeld, Raymond, 1952- (Titan Comics, 2017)
"Against his will, the idle but brilliant Mycroft Holmes is pulled into a globe-spanning adventure at the behest of Queen Victoria. A madman has stolen a handbook full of plans for civilization-destroying weapons -- and desires to sell them to the highest bidder. Can the smartest man in England track down and defeat the one foe that may prove to be his match?" -- Page [4] of cover.